Molecular and Biochemical Basis of Fluoroquinolones-Induced Phototoxicity—The Study of Antioxidant System in Human Melanocytes Exposed to UV-A Radiation - Kowalska, Justyna (Int J Mol Sci, 2020)
Phototoxicity of fluoroquinolones is connected with oxidative stress induction. Lomefloxacin (8-halogenated derivative) is considered the most phototoxic fluoroquinolone and moxifloxacin (8-methoxy derivative) the least. Melanin pigment may protect cells from oxidative damage. On the other hand, fluoroquinolone–melanin binding may lead to accumulation of drugs and increase their toxicity to skin. The study aimed to examine the antioxidant defense system status in normal melanocytes treated with lomefloxacin and moxifloxacin and exposed to UV-A radiation. The obtained results demonstrated that UV-A radiation enhanced only the lomefloxacin-induced cytotoxic effect in tested cells. It was found that fluoroquinolones alone and with UV-A radiation decreased superoxide dismutase (SOD) activity and SOD1 expression. UV-A radiation enhanced the impact of moxifloxacin on hydrogen peroxide-scavenging enzymes. In turn, lomefloxacin alone increased the activity and the expression of catalase (CAT) and glutathione peroxidase (GPx), whereas UV-A radiation significantly modified the effects of drugs on these enzymes. Taken together, both analyzed fluoroquinolones induced oxidative stress in melanocytes, however, the molecular and biochemical studies indicated the miscellaneous mechanisms for the tested drugs. The variability in phototoxic potential between lomefloxacin and moxifloxacin may result from different effects on the antioxidant enzymes.